Amplified sinus-P-wave analysis predicts outcomes of cryoballoon ablation in patients with persistent and long-standing persistent atrial fibrillation: A multicentre study - Creta, Antonio; Venier, Sandrine; Tampakis, Konstantinos; Providencia, Rui; Sunny, Juno; Defaye, Pascal; Earley, Mark J.; Finlay, Malcolm; Hunter, Ross J.; Lambiase, Pier D.; Papageorgiou, Nikolaos; Schilling, Richard J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Outcomes of catheter ablation for non-paroxysmal atrial fibrillation (AF) remain suboptimal. Non-invasive stratification of patients based on the presence of atrial cardiomyopathy (ACM) could allow to identify the best responders to pulmonary vein isolation (PVI). Methods: Observational multicentre retrospective study in patients undergoing cryoballoon-PVI for non-paroxysmal AF. The duration of amplified P-wave (APW) was measured from a digitally recorded 12-lead electrocardiogram during the procedure. If patients were in AF, direct-current cardioversion was performed to allow APW measurement in sinus rhythm. An APW cut-off of 150ms was used to identify patients with significant ACM. We assessed freedom from arrhythmia recurrence at long-term follow-up in patients with APW150ms vs. APW<150ms. Results: We included 295 patients (mean age 62.310.6), of whom 193 (65.4%) suffered from persistent AF and the remaining 102 (34.6%) from long-standing persistent AF. One-hundred-forty-two patients (50.2%) experienced arrhythmia recurrence during a mean follow-up of 793±604 days. Patients with APW150ms had a significantly higher recurrence rate post ablation compared to those with APW<150ms (57.0% vs. 41.6%; log-rank p<0.001). On a multivariable Cox-regression analysis, APW150ms was the only independent predictor of arrhythmia recurrence post ablation (HR 2.03 CI95% 1.28-3.21; p=0.002). Conclusion: APW duration predicts arrhythmia recurrence post cryoballoon-PVI in persistent and long-standing persistent AF. An APW cut-off of 150ms allows to identify patients with significant ACM who have worse outcomes post PVI. Analysis of APW represents an easy, non-invasive and highly reproducible diagnostic tool which allows to identify patients who are the most likely to benefit from PVI-only approach.